Exordia [large type] - Dickinson, Seth (Thorndike Press large print top shelf, 2024)
"Anna Sinjari--refugee, survivor of genocide, disaffected office worker--has a close encounter that reveals universe-threatening stakes. Enter Ssrin, a many-headed serpent alien who is on the run from her own past. Ssrin and Anna are inexorably, dangerously drawn to each other, and their contact reveals universe-threatening stakes. While humanity reels from disaster, Anna must join a small team of civilians, soldiers, and scientists to investigate a mysterious broadcast and unknowable horror. If they can manage to face their own demons, they just might save the world"--